Effective weak Hamiltonian for the Δb =1nonleptonic decays in the six-quark model (1981)
ABSTRACT: Quantum-chromodynamic corrections and flavor-symmetry-breaking effects are considered in the leadinglogarithmic approximation for the calculation of the db = 1 nonleptonic effective weak Hamiltonian in the context of the Kobayashi-Maskawa model. It is found that flavor-symmetry breaking is very important for the cases under consideration here.